Comparison of different plerixafor-based strategies for adequate hematopoietic stem cell collection in poor mobilizers - Sadri, Sevil; Yönal Hindilerden, İpek and Mutlu, Yaşa Gül and Tiryaki, Tarık Onur and Gemici, Ali İhsan and Bekoz, Huseyin Saffet and Gökmen Sevindik, Ömür and Hindilerden, Fehmi and Kalayoğlu-beşışık, Sevgi and Nalçacı, Meliha and Sargın, Deniz (The European Research Journal, 2023)
Objectives: The main objective of the present study was to evaluate whether the use of plerixafor in combination with granulocyte colony-stimulating factor (G-CSF) or subsequent use of isolated G-CSF and then plerixafor following disease-specific chemotherapy, and whether it would allow for adequate peripheral stem cell collection in patients. Methods: The retrospective study evaluated 54 patients with previous mobilization failure who were administered plerixafor in 2 centers. In patients without any side effects, CD 34+ cell counts, the percentage of patients who were found eligible for autologous transplantation, the engraftment kinetics of the patients who underwent transplantation, and their overall survival results were compared between the two groups where G-CSF was used with plerixafor, or where plerixafor was used after isolated G-CSF following chemotherapy. Results: The median age of the patients was 49 years (range: 17-70), and 64.8% (n = 35) were males. It was identified that 31 (57.4%) patients underwent mobilization treatment with isolated G-CSF and plerixafor, and 23 (42.6%) patients underwent mobilization treatment with chemotherapy plus G-CSF and plerixafor. In all patients, mean hemoglobin level (11.3 ± 1.5 g/dL vs. 9.3 ± 1.3 g/dL; p < 0.001) and median platelet level (129.2 ×103/µL vs. 58.4 ×103/µL) were found to be higher, while febrile neutropenia rate (3.3% vs. 60.9%), the percentage of replacement patients (6.7% vs. 65.2%), and median days of G-CSF (6 vs. 9) were found to be lower on the day of plerixafor administration in the isolated G-CSF and plerixafor group compared to the chemotherapy and G-CSF and plerixafor group. Conclusions: In conclusion, our study demonstrated that administration of plerixafor is generally safe and well-tolerated. Regardless of the underlying disease, it offers an effective alternative for patients with previous failed mobilization attempts using conventional regimens, and allows stem cell collection with fewer apheresis sessions.